VARIASI KECEPATAN PEMOTONGAN PROSES PEMBUBUTAN BAJA AISI 4140 TERHADAP KEAUSAN DAN UMUR MATA PAHAT KARBIDA - Sobron Y. Lubis; Sofyan Djamil; Adianto Adianto; Amor Santosa; Edric VM. (Program Studi Teknik Mesin Universitas Tarumanagara, 2021)
In the machining process, increased production can be done by increasing the use of cuttingparameters. However, the use of high cutting parameters has an effect on the wear of the cutting toolused. The aim of this research is to analyze the wear and tear that occurs on cutting tools and tool lifewhen cutting AISI 4140 steel by using variations in cutting speed. The machining process uses a CNClathe by turning the surface of the AISI 4140 steel workpiece. The wear criteria are determined when thecutting tool has reached the edge wear limit (VB) of 0.3 mm. Observation and measurement of carbidecutting tools are carried out every 5 minutes the machining process is carried out. If the cutting tool hasnot shown the specified wear value, then the cutting tool then cuts, so that the wear value is obtained.From the research conducted it was found that at a cutting speed of 160 m / min the cutting tool iscapable of cutting for 39 minutes, 13 seconds. At a cutting speed of 180 m / min the cutting tool is capableof cutting for 38 minutes, 14 seconds. At a cutting speed of 200 m / min the cutting tool is capable ofcutting for 33 minutes, 8 seconds. At a cutting speed of 240 m / min the cutting tool is capable of cuttingfor 26 minutes, 3 seconds. Taylor's advanced tool life for the coated carbide cutting tool in turning AISI4140 steel material is: Vc. Tl.0.073 = 8203.